2020
DOI: 10.3390/ijms21228712
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Calcimimetics on Osteoclast–Osteoblast Crosslink in Chronic Kidney Disease and Mineral Bone Disease

Abstract: We have previously demonstrated calcimimetics optimize the balance between osteoclastic bone resorption and osteoblastic mineralization through upregulating Wingless and int-1 (Wnt) signaling pathways in the mouse and cell model. Nonetheless, definitive human data are unavailable concerning therapeutic effects of Cinacalcet on chronic kidney disease and mineral bone disease (CKD-MBD) and osteoclast–osteoblast interaction. We aim to investigate whether Cinacalcet therapy improves bone mineral density (BMD) thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The authors noted an inverse correlation between serum alkaline phosphatase level and coronary artery calcium (CAC) score, suggesting that the selective cessation of osteoclasts, along with intact osteoblast function and a high bone turnover rate, might create a reverse calcium paradox. This could lead to regressed ectopic calcification, stabilized vascular calcification, and increased bone mass [ 30 , 31 ]. However, our 2-year study found no significant changes in CAC.…”
Section: Discussionmentioning
confidence: 99%
“…The authors noted an inverse correlation between serum alkaline phosphatase level and coronary artery calcium (CAC) score, suggesting that the selective cessation of osteoclasts, along with intact osteoblast function and a high bone turnover rate, might create a reverse calcium paradox. This could lead to regressed ectopic calcification, stabilized vascular calcification, and increased bone mass [ 30 , 31 ]. However, our 2-year study found no significant changes in CAC.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, CKD-MBD therapies focused mainly on mineral-PTH hormone-vitamin D axis, such that UVC-associated mortality remains at the top of leading causes in CKD population. Hung et al reported that CKD patients with secondary hyperparathyroidism increased expression of sclerostin that inhibits Wnt 10b/Wnt 16 signaling pathway, leading to activating osteoclastic bone resorption (tartrate-resistant acid phosphatase isoform 5b) and inactivating osteoblastic bone formation (procollagen type I propeptides), bone inflammation and low bone density, and ultimately adverse clinical events [ 25 ]. In light of this, PCS-driven UVC remains intractable.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease-mineral bone disorder (CKD-MBD) is an intricate systemic complication in CKD patients with abnormal mineral and bone metabolism, typically manifested by dysregulated circulating levels of calcium and phosphorus, intact parathyroid hormone (iPTH), vitamin D, impaired skeletal health and vascular or ectopic soft tissue calcification [ 1 ]. Patients with later stages of CKD are doomed to suffer from lower bone mineral density, leading to strikingly higher risk of bone fracture (BF) and subsequent morbidity and mortality [ 2 ]. As CKD declines, failing renal clearance results in retention of organic compounds and anorganic substances (e.g., phosphate), also referred to as uremic solutes [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%